The complex interaction between human resources management, the labor market and employment relations in Brazil - Marcus Vinicius Gonçalves da Cruz; Amyra Moyzes Sarsur; Wilson Aparecido Costa de Amorim; André Luiz Fischer; Michele Ruzon Kassem (Tourism & Management Studies)
This article reports results of qualitative research that examines how the literature available of human resource management (HRM) addresses the new characteristics of employment in Brazil in the 2000-2015 period; with an aging population, a reduction in the share of young people and increased educational level of the workforce, a drop in the number of non-employed, higher income for workers and a high rate of turnover. In employment relations, the trade unions obtained real raises above inflation and strikes have returned. Through a panel of specialists and literature on human resources management in Brazil, the study reveals a distance between the subjects of labor market, employment relations and HRM. Two hypotheses could explain these findings: (H1) labor relation and labor market issues are of little value to HRM; and (H2) HRM and employment relations are treated as different professional areas and fields of knowledge, and are poorly integrated in organizations